ON POLITICS AND VALUES - Razma, Ainis (Politologija, 2015)
The article is a response to prof. Alvydas Jokubaitis’s views on a relationship between politics and values, laid down in his paper Politics Without Values in one of the issues of Politologija journal. Ainis Razma provides different view on the issue, arguing that values and politics are the parts of a single system, where the former assumes a role of elements, while the latter is a process.The author starts from defining both politics, and values. In his view both are phenomena, not things, therefore cannot exist objectively, i.e. independently from a subject. Consequently, both politics, and values come to existence only due to some external sources of meaning. The relationship between politics and values is being explored within a context of a temporal structure of experience and activity, as it is formulated by Niklas Luhmann. Whereby it is made a conclusion that politics and values are connected not temporarily but logically.Arguing that politics is simply a public endeavour aimed at achieving or implementing certain public goals, A. Razma at the same time insists politics being one of the most fundamental societal processes reflecting on a society as a whole, and thus playing a key role in delineating public and private spaces within a particular society which in turn serves as a precondition of the construction of norms.The author reflects on the professor’s A. Jokubaitis interpretations of Hobbes and Rawls writings. Concerning the former, it is stressed that a mechanical approach to the politics, treating it as a “tool”, does not deny its relationship with values. This is argued through the notion that “instrument” always presupposes a goal whose definition is in turn inevitably influenced by values. Concerning Rawls, it is argued that an idea of morally neutral justice does not mean amorality. On the contrary, it calls for the search for or a construction of moral principals that are equally acceptable for all members of a society, and then laying them down at the foundation of a common, i.e. political justice.The author concludes that politics through the function of ideology creates, assesses, and manages values. The value may acquire its “political” quality if it appears within the public space, i.e. if a society declared it to be a value. Therefore, “political” does not refer to the nature of value, but to the area of its application. On the other hand, the values that make a common ethics of a particular society are all by definition political.